Changes and correlation of microorganism and flavor substances during persimmon vinegar fermentation. (April 2022) - Wang, Dahong; Wang, Mengyang; Cao, Luwei; Wang, Xiaotong; Sun, Jianrui; Yuan, Jiangfeng; Gu, Shaobin
Abstract: To investigate the microbial diversity and the change of the flavor substances during the traditional natural persimmon vinegar fermentation, two group samples from alcohol fermentation stage (A) and acetic acid fermentation stage (B) were analyzed. The results showed that Burkholderia, Lactobacillus, Acetobacter, Komagataeibacter were the main bacteria, and the major fungi were Saccharomyces, Hanseniaspora, Hortaea, and Cladosporium at the genus level. The contents of flavonoids and polyphenols in B increased by 17.91% and 26.59% compared with A, respectively. The superoxide anion scavenging activity significantly increased by 20.15%. The contents of total free amino acids were 5709.99 ± 410.36 mg/L and 5736.16 ± 472.02 mg/L, and the total contents of 9 organic acids were 19.89 ± 1.20 g/L and 33.77 ± 2.49 g/L in samples A and B, respectively. Pearson correlation analysis showed that 11 flavor compounds were related to Lactobacillus and Leuconostoc ; 8 and 10 compounds were respectively related to Komagataeibacter and Acetobacter ; 13 and 19 flavor compounds were respectively associated with Saccharomyces and Monascus . Orthogonal Partial Least Square (OPLS) model showed that the contents of Leu, Lys, and lactic acid were mainly associated with fungi, and γ-aminobutyric acid (GABA) content was correlated with Lactobacillus, Acetobacter, Leuconostoc, and Saccharomyces . This study revealed the relationship between microbial diversity and flavor compounds in persimmon vinegar produced by spontaneous fermentation. The results can provide a theoretical support for the safety and health assessment of persimmon vinegar. Graphical abstract: Image 1 Highlights: Illustrating the microbial diversity in the spontaneous persimmon vinegar fermentation at different fermentation stage. Studying the change of flavonoids, polyphenols, antioxidant capacity and related flavor substances. Revealing the relationship between the microbial diversity and flavor metabolites in the persimmon vinegar fermentation.